Asynchronous dan Engaged Learning Terhadap Minat Anak-Anak Mengikuti Sekolah Minggu: The Use of Asynchronous and Engaged Learning to Generate Children's Interest in Sunday School - Lidia Susanti; Kiki Pawestri Ayuningtyas (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
During the pandemic, Sunday School activities have challenges: Sunday school teachers are not familiar with technology, children are not used to technology and online meetings. This research was conducted by simple random sampling in several churches in East Java in the Middle class. The total population is 60 children, and the sample taken is 52 children. Data analysis measures the relationship between variables using a correlation test and the magnitude of the influence between variables. This study shows that a teacher can start the Sunday school activities with asynchronous learning during the pandemic using YouTube and WhatsApp media combined with engaged learning strategies that can make children feel involved.